A gene-by-sex interaction for nicotine reward: evidence from humanized mice and epidemiology - Bernardi, Rick E.; Laucht, Manfred; Spanagel, Rainer; Sommer, Wolfgang H. (Translational Psychiatry, 2016)
It has been proposed that vulnerability to nicotine addiction is moderated by variation at the μ-opioid receptor locus (OPRM1), but results from human studies vary and prospective studies based on genotype are lacking. We have developed a humanized mouse model of the most common functional OPRM1 polymorphism rs1799971_A>G (A118G). Here we use this model system together with a cohort of German youth to examine the role of the OPRM1 A118G variation on nicotine reward. Nicotine reinforcement was examined in the humanized mouse model using i.v. self-administration. Male (n=17) and female (n=26) mice homozygous either for the major human A allele (AA) or the minor G allele (GG) underwent eight daily 2 h sessions of nicotine self-administration. Furthermore, male (n=104) and female (n=118) subjects homozygous for the A allele or carrying the G allele from the Mannheim Study of Children at Risk were evaluated for pleasurable and unpleasant experiences during their initial smoking experience. A significant sex-by-genotype effect was observed for nicotine self-administration. Male 118GG mice demonstrated higher nicotine intake than male 118AA mice, suggesting increased nicotine reinforcement. In contrast, there was no genotype effect in female mice. Human male G allele carriers reported increased pleasurable effects from their first smoking experience, as compared to male homozygous A, female G and female homozygous A allele carriers. The 118G allele appears to confer greater sensitivity to nicotine reinforcement in males, but not females.